Comparative Assessment of Guidewire and Microcatheter vs a Crossing Device–Based Strategy to Traverse Infrainguinal Peripheral Artery Chronic Total Occlusions. (August 2015) - Banerjee, Subhash; Sarode, Karan; Patel, Apurva; Mohammad, Atif; Parikh, Roosha; Armstrong, Ehrin J.; Tsai, Shirling; Shammas, Nicolas W.; Brilakis, Emmanouil S.
Purpose: To compare success rates of a guidewire and microcatheter strategy vs the use of specialized crossing devices to traverse infrainguinal peripheral artery chronic total occlusions (CTOs).Methods: For this analysis, data on 438 consecutive infrainguinal CTO interventions in 438 patients (mean age 63.2 years; 402 men) performed between August 2006 and May 2014 were extracted from the multicenter Excellence in Peripheral Artery Disease ( XL PAD) database ( ClinicalTrials.gov ; identifier NCT01904851). Primary technical success constituted placement of a guidewire in the true lumen, past the distal CTO cap, with the initial crossing strategy.Results: A wire-catheter strategy was used in 295 (67.4%) and a specialized CTO crossing device in 143 (32.6%) patients (p<0.001). Primary crossing technical success was higher with CTO devices (72.1% vs 51.9%, p<0.001). The primary wire-catheter arm used significantly more secondary CTO devices (28.1% vs 17.5%) and/or provisional re-entry devices (26.7% vs 4.9%) compared with the primary CTO device arm (both p<0.001). Secondary crossing technical success (defined as crossing with an alternate strategy: 67.5% vs 71.4%, p=1.000), provisional crossing technical success (defined as use of a re-entry device: 84.2% vs 87.5%, p=0.768), and procedure success (93.6% vs 90.9%, p=0.332) were similar between the wire-catheter and CTO device strategies, respectively. No differences were observed in periprocedural complications or 30-day adverse events; however, at 12 months, there was a significantly higher surgical revascularization rate in the primary wire-catheter arm (8.8% vs 2.8%, p=0.025).Conclusion: Infrainguinal peripheral artery CTO crossing is frequently attempted with a wire-catheter technique; however, an initial CTO crossing device approach is associated with higher primary technical success. Overall procedure success is similar with both strategies.